1981
DOI: 10.2136/sssaj1981.03615995004500060015x
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamics of Ternary Cation Exchange Systems and the Subregular Model

Abstract: The thermodynamic theory of ternary exchange equilibria is developed. It is shown that the analogs of well‐known thermodynamic expressions for binary exchange systems can be derived for ternary systems as well. The subregular model of ternary cation exchange systems, which was applied recently to NH4‐Ba‐La exchange on montmorillonite, is examined critically within the thermodynamic context. It is found that the subregular model for a ternary system cannot be expressed solely in terms of parameters that depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 0 publications
1
28
0
Order By: Relevance
“…Modeling the variation of the selectivity coefficient The subregular solution model introduced by Elprince et al (1980) and Chu and Sposito (1981) to descri be the variation of the exchanger phase activity coefficients in ternary exchange systems contains a model parameter which needs to be determined from ternary experimental data. Fletcher et al (1984), Sposito et al (1983), and Sposito and Fletcher (1985) showed that the magnitude of the parameter is negligible in view of the experimental error involved in the determination of the equilibrium ionic composition.…”
Section: Ternary Exchangementioning
confidence: 99%
“…Modeling the variation of the selectivity coefficient The subregular solution model introduced by Elprince et al (1980) and Chu and Sposito (1981) to descri be the variation of the exchanger phase activity coefficients in ternary exchange systems contains a model parameter which needs to be determined from ternary experimental data. Fletcher et al (1984), Sposito et al (1983), and Sposito and Fletcher (1985) showed that the magnitude of the parameter is negligible in view of the experimental error involved in the determination of the equilibrium ionic composition.…”
Section: Ternary Exchangementioning
confidence: 99%
“…This restriction in the thermodynamics of ion exchange was removed by Chu and Sposito (1981) who extended these general thermodynamic relations so Present address: Division of Soils and Agronomy, Regional Agricultural Research Center, Bombuwela, Kaltara, Sri Lanka. that activity coefficients in ternary cation exchange systems could be computed from relevant experimental data.…”
mentioning
confidence: 99%
“…(5). One is the popular method of fitting a polynomial to plots of K v as a function of composition and then integrating the polynomial (Barri and Rees, 1980;Sposito, 1981;Chu and Sposito, 1981). The result of this integration is the K eq .…”
Section: Test Datamentioning
confidence: 99%
“…There are a number of models available for the activities of the solid-phase ions (Truesdell 1966;Smith and Woodburn, 1978;Chu and Sposito, 1981;Pabalan, 1994;Bond, 1995;Snyder and Cavallaro, 1997), all of which have some empirically determined parameters. This study uses the class of polynomials introduced by Cox (1971) to model mixtures, augmented with the inverse-terms model proposed by Draper and St. John (1977).…”
Section: Solid-phase Activity Coefficient Modelsmentioning
confidence: 99%
See 1 more Smart Citation